Sidelobe reduction of large-scale antenna array for 5G beamforming via hierarchical cuckoo search - Sun, Geng; Liu, Yanheng; Li, Jionghui; Zhang, Ying; Wang, Aimin (Electronics letters, 2017)
Large-scale antenna array (LSAA) is one of the key factors as well as a fundamental technology in fifth generation wireless communication systems. Beampattern sidelobe (SL) suppressing is a complex nonlinear optimisation problem, especially for LSAAs, because of the high-dimensional solution space. A SL reduction method for LSAA based on a hierarchical cuckoo search (HCS) algorithm is proposed. HCS divides the candidate solutions into different levels to improve population utilisation, so that it is suitable for dealing with large-scale elements. The effectiveness of the proposed method for synthesis of the beampattern of LSAA is verified by theoretical and EM simulations.